DERMOSCOPY OF ORAL SQUAMOUS CELL CARCINOMA - Bajpai, Manas; Gupta, Suresh (Journal of Ayub Medical College Abbottabad, 2018)
A 67 year old lady presented with the chief complaint of painful nodular ulcerative mixed red and white colored lesion of the tongue from 8 months Personal history of the patient revealed that she has been smoking 10 - 12 cigarettes per day since 27 years. No systemic complications were found. Intra - oral examination revealed a leuko - erythroplakik, non - scrapable lesion of the dorsum surface of the tongue extending to the right lateral border, measuring about 2 Ã— 2 cm. [Figure 1] On palpation the lesion was indurated and soft to firm in consistency. A significant color variegation in the lesion was found with the admix of white and red areas. Cervical group of lymph nodes of the patient was non palpable. On the basis of clinical features a provisional diagnosis of leukoplakia was given. A 67-year-old lady presented with the chief complaint of painful nodular ulcerative mixed red and white coloured lesion of the tongue from 8 months Personal history of the patient revealed that she has been smoking 10-12 cigarettes per day for 27 years. No systemic complications were found. Intra - oral examination revealed a leuco-erythro-plakic, non - scrapable lesion of the dorsum surface of the tongue extending to the right lateral border, measuring about 2Ã—2 cm. [Figure-1] On palpation the lesion was indurated and soft to firm in consistency. A significant colour variegation in the lesion was found with the admix of white and red areas. Cervical group of lymph nodes of the patient was non-palpable. On the basis of clinical features, a provisional diagnosis of leucoplakia was given. Dermoscopic examination revealed a central structure less area with white circles with some ulcerated areas showing blood spots surrounded by polymorphous linear coiled blood vessels, these vessels were found to be surrounded by white halo at places, at some places the white circles were centred on a dilated cavity filled with keratin plug [Figure-2 A and B] The pictures were taken with DermLite DL3 dermoscope (polarizing and nonpolarizing mode) coupled to an Olympus E-450 camera (Olympus Corporation). Based on dermoscopic features a final diagnosis of oral squamous cell carcinoma was rendered and the patient was referred to the department of Oral and maxillofacial surgery for the treatment. Histopathological examination of the tissue section showed a connective tissue stroma densely infiltrated with the islands of severely dysplastic cells and collections of numerous keratin pearls. [Figure-3] The final diagnosis of well differentiated squamous cell carcinoma was given. Dermoscopic features of squamous cell carcinoma (SCC) were described by Rosendahl et al in 2012.1 The features include white circles, blood spots and white structure less zone. The white circles were found to be the most potent feature and were found to be positive in 87% cases of SCC. These white circles correspond to acanthosis and hypogranulosis of infundibular epidermis. Although pattern of blood vessels was not found to be significant in their study but they can be significant for the clinical diagnosis. The present case showed white circles, blood spots showing ulcerative areas and white structure less zone, dilated infundibulum filled with keratin plug and a prominent course of polymorphous linear blood vessels; hence a preliminary diagnosis of SCC was given, which was confirmed by histopathological examination. Despite the increased usefulness of dermoscopy in dermatological lesions, the method is not very popular in investigating oral mucosal lesions.2,3 There is a paucity of cases describing dermoscopic features of oral squamous cell carcinoma. This paper presents dermoscopic features of oral SCC. The diagnosis was confirmed by histopathology. It can be concluded that dermoscopy in oral lesions allows clinician to minimize the risk of the exposure of the patient to biopsy that may be resulting in facial disfigurement but dermoscopy cannot be used as a sole diagnostic tool especially in malignancy, it can be used for screening purposes. There is a need to intensify the research pertaining to the use of dermoscopy in oral mucosal lesions considering the increased prevalence of oral cancer. Dermoscopy can become a very useful screening tool for oral cancers.